An Needs Analysis of The Development of The Thematic E-Module by Using Savi Approach - Ros Dwi Armiyanti; Djalal Fuadi; Anatri Desstya; Yeny Prastiwi (STAI Hubbulwathan Duri, 2022)
Online learning during the Covid-19 pandemic experienced several obstacles, one of which students have difficulty following asynchronous learning. The purpose of research to analyze the need for the development of the thematic e-module based on SAVI approach with the assistant of the Sway application. This research is a RD 4D model development which is limited to define stage. Research Respondents are 29 Grade 5 teachers in Bendosari District, Sukoharjo District selected by Stratified Random Sampling. The time of preparation was conducted in November 2021 to March 2022. Data was taken through questionnaires, interviews, and literature studies. Test valuation of data using credibility test and confirmability test. Technique of data analysis are using Miles and Huberman model consisting of data reduction, display data, and conclusion / verification. Based on the results of data analysis in the concerned there is a need for the development of thematic e-module with SWAY-assisted SAVI approach to accommodate various student learning styles: Somatis, Audio, Visual, and Intellectual as an alternative of asynchronous learning.